Adequacy of nutritional intake during pregnancy in relation to prepregnancy BMI: results from the 3D Cohort Study - Dubois, Lise; Diasparra, Maikol; Bédard, Brigitte; Colapinto, Cynthia K.; Fontaine-Bisson, Bénédicte; Tremblay, Richard E.; Fraser, William D. (Université d'Ottawa | University of Ottawa, 2018)
Our study compares adequacy of nutritional intakes among pregnant women with different prepregnancy BMI and explores associations between nutritional intakes during pregnancy and both prepregnancy BMI and gestational weight gain (GWG). We collected dietary information from a large cohort of pregnant Canadian women (n 861) using a 3-d food record. We estimated usual dietary intakes of energy (E), macronutrients and micronutrients using the National Cancer Institute method. We also performed Pearson's correlations between nutritional intakes and both prepregnancy BMI and GWG. In all BMI categories, intakes considered suboptimal (by comparison with estimated average requirements) were noted for Fe, vitamin D, folate, vitamin B6, Mg, Zn, Ca and vitamin A. Total fat intakes were above the acceptable macronutrient distribution range (AMDR) for 36 % of the women. A higher proportion of obese women had carbohydrate intakes (as %E) below the AMDR (v. normal-weight and overweight women; 19 v. 9 %) and Na intakes above the tolerable upper intake level (v. other BMI categories; 90 v. 77-78 %). In all BMI categories, median intakes of K and fibre were below adequate intake. Intakes of several nutrients (adjusted for energy) were correlated with BMI. Correlations were detected between energy-adjusted nutrient intakes and total GWG and were, for the most part, specific to certain BMI categories. Overweight and obese pregnant women appear to be the most nutritionally vulnerable. Nutrition interventions are needed to guide pregnant women toward their optimal GWG while also meeting their nutritional requirements.
Keywords: AMDR acceptable macronutrient distribution range; GWG gestational weight gain; IOM Institute of Medicine; UL tolerable upper intake level; Diets; Gestational weight gain; Nutrition; Pregnancy; Prepregnancy BMI